On the Justification Problems: Towards a Peircean Diagnosis and Solution. Issue 3 (3rd July 2017) - Zhang, Liuhua
Abstract : Responding to the paradox of inference and the related problems in philosophy of logic, this paper argues for the necessity of distinguishing between two different objects of justification: logica utens and logica docens . Then, equipped with Peirce's critical common-sensist conception of logica utens and his classification of sciences, I propose a diagnosis of and a solution to the problem of justification of logic. I argue that this alternative approach successfully avoids circularity in which most attempts in philosophy of logic have been inescapably trapped. I also anticipate and respond to possible objections to taking a Peircean turn in justifying logic.